Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

Thick-shelled, grazer-protected diatoms decouple ocean carbon and silicon cycles in the iron-limited Antarctic Circumpolar Current - Assmy, Philipp; Smetacek, Victor; Montresor, Marina; Klaas, Christine; Henjes, Joachim; Strass, Volker; Arrieta, Jesus M; Bathmann, Ulrich; Berg, Gry Mine; Breitbarth, Eike; Cisewski, Boris; Friedrichs, Lars; et al. (Proceedings of the National Academy of Sciences, 2013)
Diatoméer – alger med skall av silisium, som er helt avhengige av næringsstoffet silikat – dominerer fytoplankton oppblomstringer og spiller en nøkkelrolle i havets økosystemer og i global karbonsyklus. Vi viser hvordan forskjeller i økologiske karakteristikker av dominerende arter i Sørishavet, som ble observert under det in situ europeiske jerngjødslings eksperimentet (European Iron Fertilization Experiment - EIFEX), kan påvirke karbon og silisium syklusene i havet. Vi argumenterer for at økologien til tykkskallete diatomé arter, som er selektert for av sterk beiting fra kopepoder, tar opp silikat fremfor andre næringsstoffer i det dype Sørishavet og underliggende sedimenter. Fordi Sørishavet er en viktig sentral for oseanisk fordeling av næringsstoffer, selektivt opptak av silikat i dette havområdet begrenser oppblomstringene av diatoméer i andre deler av verdenshavene, noe som potensielt får konsekvenser for biotisk opptak av karbon i hele verdens havområder.
Keywords: Sørishavet; marinbiologi; oseanografi; plankton; økosystem

Tintinnid ciliates of Amundsen Sea (Antarctica) plankton communities - Dolan, John R; Yang, Eun Jin; Lee, Sang Hoon; Kim, Sun Young (Polar Research, 2013)
The Amundsen Sea has been described as one of the most productive and dynamic pelagic systems in Antarctica and is one of the least studied. Based on samples from 15 stations in the Amundsen Sea, we describe for the first time the composition of the tintinnid ciliate assemblage of the microzooplankton. We compared the species compositions of coastal polynya sites, where the phytoplankton communities are dominated by Phaeocystis, to those of the offshore deep water sites, which are dominated by diatoms. We found a total of 15 species. Polynya sites were dominated by a few species of tintinnids, mostly those endemic to the Southern Ocean. In contrast, the deep-water sites contained many widespread tintinnid species, which are known from a wide variety of systems as well as other areas of the Southern Ocean. We examined polymorphism known to characterize the Antarctic tintinnid species Cymatocylis affinis/convallaria and Codonellopsis gaussi. We found that the types or forms found appeared unrelated to the type of microplankton community, defined by the identity of the dominant phytoplankton taxa. However, the number of different morphotypes found at a site appeared related to the overall concentration of the species, suggesting that different morphologies, previously considered distinct species, may simply be developmental stages. Keywords: Zooplankton; microzooplankton; polynya; protists; Phaeocystis; diatoms.
Keywords: Sørishavet; diatomeer; fytoplankton; marin biologi; oseanografi; protoktister; zooplankton; økologi

Microbial biogeography during austral summer 2007 in the surface waters around the South Shetland Islands, Antarctica - Olsen, Lasse Mork; Ardelan, Murat van; Hewes, Christopher D; Holm-Hansen, Osmund; Reiss, Christian; Bizsel, Nihayet; Sakshaug, Egil; Vadstein, Olav (Aquatic Microbial Ecology, 2013)
Recent studies have concluded that different water bodies in the ocean can contain different microbial communities. The goal of the present study was to determine if biogeographic patterns are present for aquatic microbes in waters which meet around the South Shetland Islands(SSI), Antarctica. Prokaryotic and eukaryotic marine microbial communities were monitored during the 2007 austral summer by use of polymerase chain reaction (PCR) and denaturing gradientgel electrophoresis (DGGE) of small subunit ribosomal DNA. Hydrographic properties, nutrients and chlorophyll a were also measured. There was an onshore to offshore gradient in temperature, salinity and iron concentration and a unimodal distribution of chlorophyll a concentration in rela-tion to the middle of this gradient that occurred near the SSI. The differences in microbial community structure among stations in the studied area were correlated with both geographical distance and environmental factors. For eukaryotes, the correlation was strongest for environment, where as it was strongest for geographical distance for the prokaryotes. Eukaryotic and prokaryotic community structures were highly correlated. Surface water from the Weddell Sea had a different community of eukaryotes than the water in the Antarctic Circumpolar Current in the Drake Passage, whereas the prokaryotic community was not significantly different. The area close to theSSI where the 2 water types mix had the highest chlorophyll concentration and significantly dif-ferent communities of eukaryotes and prokaryotes from both of the inflowing water types. These results suggest that the prokaryote community structure was more affected by productivity thanby environmental variables. KEY WORDS: Microbial biogeography. Microbial community. Natural iron enrichment. Southern Ocean.
Keywords: Sørishavet; biogeografi; marin biologi; mikroorganismer; oseanografi; overflatevann; økosystemer

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Circulation and exchanges at high-latitude ocean margins : dynamical models and observations from instrumented seals - Zhou, Qin; Eltoft, Torbjørn (UiT The Arctic University of Norway, 2013)
Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf cavity after being brought on-shore by wind-driven surface Ekman transport, and being spread below the depth of the ice base within a regime of coastal downwelling. The results also suggest a complex picture of water mass exchange processes along the coast of Eastern Weddell Sea, in which mesoscale eddies play a central role. Finally, the data collected by the seals are employed to evaluate the performance of a global coupled ocean-ice model incorporated with a parametrization of wave-induced mixing in simulating the upper ocean properties in the Southern Ocean. The results suggest that wave-induced mixing is important to modify the upper ocean properties. Since coastal water properties in the Eastern Weddell Sea are mainly determined by the onshore Ekman transport of surface waters, the wave-induced mixing also plays a role in preconditioning the coastal water masses in this region. I dette arbeidet er sirkulasjon og blandingsmekanismer i havområder på høge breddegrader undersøkt ved bruk av analytiske modeller, numeriske simuleringer og havobservasjoner. På den nordlige halvkulen er det undersøkt hvordan transport av Atlanterhavsvann etablerer seg som en topografisk styrt strøm langs kontinentalsokkelskråningen. En forenklet analytisk modell basert på geostrofisk balanse kan forklare hvordan varmetap i vannet som strømmer langs en skrånende bunn fører til en baroklin strøm på tvers av skråningen som igjen blir transformert til en barotrop strøm langs den skrånende bunnen. Denne transportendringen kan man beregne fra hydrografiske data. En slik beregnet transportendring over kontinentalsokkelskråningen vest for Skotland stemmer godt overens med observert transportendring i denne regionen. Resultatene understreker at geostrofi kan bli brukt til å diagnostisere topografisk styrte strømmer, noe som gjør teorien spesielt egnet for å studere oseanografi på høge breddegrader der topografisk styring av strømmene er mest tydelig. I det østlige Weddellhavet, i den atlantiske sektoren av Antarktis, har prosessene som styrer vannmasseutvekslingen på tvers av kontinentalsokkelskråningen blitt undersøkt ved å ta i bruk mer enn 11.000 havprofiler som er blitt samlet inn av seler i denne regionen fra februar til november 2008. Selene var utsyrt med temperatur-, salt- og dybde-loggere. Den foreslåtte mekanismen at vind-drevet nedstrømning er ansvarlig for oppsamling av antarktisk overflatevann nær isbremmen og for dens videre spredning under den flytende isbremmen langs kysten av den østlige Weddellhavet, er testet ved hjelp av en kombinasjon av detaljerte dataanalyser av observasjonene som ble samlet inn av selene, en analytisk modell og numeriske simuleringer. Resultatene viser at det antarktiske overflatevannet entrer hulområdet under isbremmen etter at det er blitt fraktet mot isbremmen som Ekman-transport i overflaten. Spredningen på undersiden av den flytende isbremmen kan forklares ved hjelp av samme mekanisme som nedstrømning langs en kyst. Resultatene tyder også på at vannmasseutvekslingen langs kysten av det østlige Weddellhavet er sammensatt av flere prosesser der virvler av mesoskala størrelse spiller en sentral rolle. Til slutt er dataene som ble samlet inn av selene blitt brukt til å evaluere en global hav-is-modell som har innebygget en parameterisering av bølgedrevet blanding i Sørhavet. Resultatene indikerer at bølgedrevet blanding er viktig for å modifisere hva de øvre vannmassene i Sørhavet er sammensatt av. Siden sammensetningen i kystvann i det østlige Weddellhavet er hovedsakelig bestemt av Ekmantransport inn mot kysten, vil bølgedrevet blanding også spille en rolle når det gjelder å danne kystvannmassene i denne regionen.
Publication Title: Universitetet i Tromsø, Fakultet for naturvitenskap og teknologi Volume: Ph.D. Issue: DOKTOR-004
Keywords: Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr